The impacts of shortening secondary school duration - Stephan L. Thomsen (IZA World of Labor, 2015)
The main goal of secondary school education in developed countries is to prepare students for higher education and the labor market. That demands high investments in study duration and specialized fields to meet rising skill requirements. However, these demands for more education are in opposition to calls for early entry to the labor market, to lengthen working lives to meet the rising costs associated with an aging population and to enable the intergenerational transfer of skills. One way to lengthen working lives is to shorten the duration of secondary school, an option recently implemented in Canada and Germany. The empirical evidence shows mixed effects.
Keywords: I21; J18; J24; C21; 330; learning intensity; compression of curricula; education choice; personality traits